THE MORAL AND AESTHETIC DEVELOPMENT OF THE LEADER'S PERSONALITY AND SOCIAL STABILITY IN THE EASTERN PHILOSOPHICAL TRADITION (International Conference on Education, Psychology and Humanities, 2026)
The article analyzes the moral and aesthetic factors that ensure social stability in the personality of a leader, based on the Eastern philosophical tradition, specifically Confucianism, Islamic ethics, and the heritage of Central Asian thinkers. Concepts such as justice, governance, self-cultivation, and the ideal of beauty are examined through a philosophical-comparative method, and their relevance to modern leadership theory is substantiated.
Keywords: Eastern philosophy, leadership ethics, social stability, aesthetic ideal, justice, Confucianism, Islamic ethics.